Penerapan Bahan Ajar Bahasa Indonesia bagi Penutur Asing (BIPA) “Sahabatku Indonesia” Tingkat Dasar di IAIN Surakarta - Dwi Kurniasih; Siti Isnaniah (Jurnal Bahasa Indonesia bagi Penutur Asing, 2019)
Abstract: This study aims to describe the application of basic level BIPA Sahabatku Indonesia teaching materials at IAIN Surakarta. The method used in this research is descriptive qualitative. The method is used to describe and explain the basic level of BIPA Sahabatku Indonesia teaching materials used in BIPA learning at IAIN Surakarta. This research requires direct study in the field to get optimal results. The place chosen to conduct research is at the BIPA institution in IAIN Surakarta which has a new BIPA institution for foreign students. Data sources are classified into two parts, namely informants and events. The results showed in the BIPA learning process in Surakarta IAIN the main teaching material used was Indonesian Friends of Primary and A1 in each class. The learning process of using teaching materials runs well and is structured according to the contents of the book. However, textbooks that are more appropriate to be used at PTKIN are still needed so that the learning objectives can run optimally. Special BIPA SKL is needed for PTKIN so that learning outcomes are in accordance with the right goals and have a clear handle, especially in the realm of Islamic Studies.